Peran Media Partner sebagai Instrumen Public Relations untuk Penguatan Citra Radio Pikiran Rakyat FM Bandung - Farida Farida; Firda Kurnia Rahman (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
This study examines the strategy of Radio Pikiran Rakyat FM (PRFM) in implementing a media partner program designed to reinforce a positive brand image and expand audience reach. Employing a descriptive qualitative methodology, data were obtained through in-depth interviews with PRFM’s internal stakeholders (General Manager, Head of Marketing Communication, Editor in Chief) and external media partners, as well as through participant observation. The findings reveal the enactment of five key image dimensions—credibility, trust, security, transparency, and engagement—strengthened by the professionalism of PRFM’s team, the flexibility of full barter and semi-barter collaboration models, and responsive communication practices. Media partners reported enhanced event exposure and expressed strong loyalty toward ongoing collaboration. Although formal evaluation currently focuses on partner retention, the introduction of quantitative and qualitative feedback mechanisms is recommended to support continuous program improvement. The study concludes that PRFM’s media partner program effectively solidifies its positive image and fosters strategic synergy while highlighting the importance of structured evaluation and the diversification of promotional platforms to optimize collaborative outcomes.